The missing pages - Watenpaugh, Heghnar Zeitlian (Stanford University Press, 2019)
In 2010, the world's wealthiest art institution, the J. Paul Getty Museum, found itself confronted by a century-old genocide. The Armenian Church was suing for the return of eight pages from the Zeytun Gospels, a manuscript illuminated by the greatest medieval Armenian artist, Toros Roslin. Protected for centuries in a remote church, the holy manuscript had followed the waves of displaced people exterminated during the Armenian genocide. Passed from hand to hand, caught in the confusion and brutality of the First World War, it was cleaved in two. Decades later, the manuscript found its way to the Republic of Armenia, while its missing eight pages came to the Getty. The Missing Pages is the biography of a manuscript that is at once art, sacred object, and cultural heritage. Its tale mirrors the story of its scattered community as Armenians have struggled to redefine themselves after genocide and in the absence of a homeland. Heghnar Zeitlian Watenpaugh follows in the manuscript's footsteps through seven centuries, from medieval Armenia to the killing fields of 1915 Anatolia, the refugee camps of Aleppo, Ellis Island, and Soviet Armenia, and ultimately to a Los Angeles courtroom. Survivor objects : artifacts of genocide – Hromkla : the God-protected castle of priests and artists – Zeytun : the lost world of Ottoman Armenians – Marash : the holy book bears witness – Aleppo : survivors reclaim their heritage – New York : the Zeytun Gospels enters art history – Yerevan : Toros Roslin, artist of the Armenian nation – Los Angeles : the contest over art
Literaturverzeichnis: Seite 371-378
Keywords: Tʻoros Ṛoslin; Illumination of books and manuscripts; Armenian; Illumination of books and manuscripts; Medieval; Christian art and symbolism; Cultural property; Manuscript fragments; Armenian massacres; 1915-1923